Broad Art Foundation - Broad Art Foundation (2009)
[Dt.:] Die Broad Art Foundation ist ein Leihgeber zeitgenössischer Kunst aus der Sammlung von Eli und Edythe Broad. Um zeitgenössische Kunst zu verbreiten, gründeten die Broads die Broad Art Foundation im Jahre 1984, so dass die Werke durch ein Leihprogramm für ausgewiesene Institutionen weltweit weiterhin in der Öffentlichkeit bleiben. - [Engl.:] The Broad Art Foundation is a lending resource of contemporary art drawn from the collections of Eli and Edythe Broad. In order to advance public appreciation for contemporary art, the Broads established The Broad Art Foundation in 1984 as a way to keep these works in the public domain through an enterprising loan program at accredited institutions throughout the world.